The Analysis of Coal Competitiveness and the Factors Affecting Indonesia's Coal Exports to Main Destination Countries (A Case of 8 Destination Countries) - Admi, Randy; Saleh, Samsubar; Fitrianto, Gigih (Universitas Airlangga, 2022)
Indonesia is one of the largest coal producers globally, with coal as the main export commodity compared to other commodities in the mining sector. The more competitive the world coal market is, the Indonesian coal market share faces threats from other coal exporting countries. The increasing commitment of countries to reduce air pollution by cutting the use of coal for power plants at PLTU. This study analyzes the competitiveness and various factors that influence the competitiveness of Indonesian coal in 8 export destination countries. This study seeks to determine how the development of Indonesia's coal competitiveness to the eight central destination countries and what factors affect Indonesia's coal exports for the 2009-2020 period to the eight central destination countries using RCA analysis and panel data regression. Based on the analysis, results show that the competitiveness of Indonesia's coal exports to 8 destination countries is excellent. It can be seen from the RCA value obtained by each country from 2009-to 2020, which is greater than 1. Meanwhile, based on the results of panel data, regression estimates with random models show that GDP per capita, population, and coal prices have a negative and significant impact on coal competitiveness in 8 Indonesian coal importing countries. The study results did not find the effect of exchange rates and CPO prices on coal competitiveness in 8 Indonesian coal importing countries.